Enhancing EFL students’ vocabulary learning through Quizizz-based formative asssessments - Hendrawaty, Nurmala; Sakhiyya, Zulfa; Wahyuni, Sri; Yuliati, Yuliati (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Mastering vocabulary is fundamental to learning English as a Foreign Language (EFL); however, students often struggle with various vocabulary components. This study aims to: (1) identify which vocabulary components show the most significant improvement in students' learning outcomes through Quizizz-based formative assessments, and (2) explore individual differences in EFL students' vocabulary performance across these assessments. This descriptive quantitative study involved 30 students from an EFL vocabulary class at a private university in Jakarta. Students completed nine Quizizz-based formative assessments covering various vocabulary topics, including word classes, word formations, synonyms, antonyms, idioms, collocations, phrasal verbs, and context-specific terms related to education and social media. The data were analysed using descriptive statistics consisting of the minimum and maximum scores, the mean, the standard deviation, and the variance. The results showed that social media and synonyms were the easiest vocabulary units because they had the highest average scores. In contrast, the units on phrasal verbs and word formations were the most challenging, as indicated by the lowest average scores. Most students demonstrated improvement across the assessments. Nevertheless, a small number of students revealed inconsistent performance across the various assessments, as evidenced by individual variability in performance. These findings suggest that Quizizz-based formative assessments can enhance students' vocabulary learning outcomes and help teacher educators design responsive instructional strategies to meet the diverse needs of EFL students.